Pedagogy of Care between Sustainability and Social Justice - Fabrizia Abbate; Caterina Braga; Alessio Fabiano; Dalila Forni; Francesca Franceschelli (Pensa MultiMedia, 2022)
Social justice comes also from care. The pedagogical lens gives us the opportunity to reflect on the deep meaning of care as: negotiation of needs (Lopez, 2017); development of the potential of others; gratuitousness and respect (Mortari, 2017). To this effect, the reflection on care extends from the subject as propagator of care, to the subject as recipient of care. In a particular way, we believe that it is possible to contribute to social justice through values supporting and protecting the environment, involving men and women, through forms of recognition and enhancement of talents, including all age groups (even the elderly, of course) and, last but not least, through the most advanced forms of technology and artificial intelligence.